Selenium levels in soil and tea as affected by soil properties in Jiangxi Province, China - Jiang, Fahui; Wu, Yan; Islam, Mahbub Ul; Jiang, Xinfeng; Wang, Binqiang; He, Shaolang; Lin, Xiaobing; Sun, Yongming; Chen, Guohui; Chen, Xi; Huang, Shangshu (BMC plant biology, 2024)
Selenium (Se) is an essential element for humans and animals, and Se deficiency-related diseases are a significant global health concern. Tea may help ameliorate Se deficiencies. However, the mechanisms of natural Se enrichment in tea remain poorly understood, particularly in high-Se soils, such as those in Jiangxi Province. This study conducted a comprehensive field survey of 67 soil and tea samples from Jiangxi, a major tea production region in China, to analysis spatial variation in Se concentrations and identify key driving mechanisms. The average soil Se concentration across Jiangxi was 0.44 mg kg , exceeding both global (0.15 mg kg ) and Chinese (0.29 mg kg ) averages. Soil Se content was significantly influenced by soil organic matter (SOM), total potassium (K), iron (FeOX) and aluminium (AlOX) oxides, and tea planting duration, contributing 15%, 6%, 20%, 22%, and 10%, respectively. Soil Se levels increased with SOM and planting duration, but decreased with total K content. Conversely, the average Se content in tea leaves was only 0.10 mg kg , and primarily driven by soil Se (29%), followed by FeOX (13%), AlOX (15%), SOM (5%), available K (5%), as well as inputs of nitrogen and K fertilizer (6% and 5% respectively), each. Partial least squares models identified four key pathways in which environment and human management practices, directly or via interactions with soil properties (SOM, K, FeOX, AlOX), influenced Se transfer from soil to tea leaves. Overall, our findings indicate that tea cultivation is more suitable in areas with high soil Se, such as central Jiangxi Province, and suggest that tea Se content can be enhanced by increasing levels of soil Se, SOM, K, FeOX, and AlOX.